Ma'ani Al-Hadits Study On Beard Sharing For Men - Putri, Azzura Mullani; Nurlizam, Nurlizam; Mustafa, Ilham (International Journal of Research, 2024)
Beards are something that is found under the chin of every human being, but in Islam maintaining this beard is a form of Islamic teaching delivered by the Prophet Muhammad SAW. But in the present era, maintaining the beard the scholars have differences in understanding it and also related to the law to shave it. This research uses a qualitative method with a ma'anil hadith study model related to the discussion of shaving beards for men. The primary data sources of this research are the books of hadith (kutubus tis'ah) and the books of hadith commentary. While the supporting sources in this study are all books, scientific articles from online journals, theses and others related to the theme of discussion. The data collection technique of this research is to trace all sources of hadith and filter the hadith according to the theme discussed. After the data is obtained, the author will present the data in the form of narratives, tables and graphs, making it easier for the author to draw a conclusion from this research. The findings of this study are that there is no single result that prohibits shaving the beard for Muslims. However, maintaining a beard is an order from the Prophet and a form of difference between Muslims and other people. While in the form of maintaining or shaving the beard is a form of a person in maintaining the appearance, so that it looks more presentable. Nowadays, there are so many innovations that can be done to shave the beard, including electronic razors, laser technology, automatic razors and quality beard care products.